PENGARUH BRAND IMAGE, BIAYA PENDIDIKAN, SOCIAL MEDIA MARKETING, TERHADAP KEPUTUSAN KULIAH DENGAN BRAND TRUST SEBAGAI VARIABEL INTERVENING - Mustofa, Agus; widodo, Agus purbo; Sudarsono, Heri (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2025)
The increasing competition among private universities in Indonesia requires higher education institutions to understand the factors that influence students' decisions in choosing where to study. This study aims to analyze the effects of Brand image, Tuition Fees, and Social media marketing on College Decision, with Brand trust as an intervening variable. The research was conducted among students at Universitas Teknologi Surabaya using a quantitative approach with Structural Equation Modeling (SEM) through AMOS software. The results indicate that Brand image and Social media marketing have a significant direct effect on College Decision, while Tuition Fees do not have a direct effect but exert an indirect influence through Brand trust. Brand trust has a strong direct effect on College Decision and serves as a significant mediator between Tuition Fees and Social media marketing on College Decision. However, Brand trust does not significantly mediate the relationship between Brand image and College Decision. These findings suggest that students’ perceptions of institutional image can directly influence their decisions without necessarily building brand trust first. The results of this study are expected to serve as a foundation for more effective and targeted higher education marketing strategies.